FAKTOR – FAKTOR PENENTU KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR ENERGI BURSA EFEK INDONESIA PERIODE 2021 – 2023 - Wijaya, Melki; Dwi Aristi, Mentari; Hetri Suriyanti, Linda (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study examines the influence of institutional ownership, independent commissioners, company size, and company growth on the financial performance of energy companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sample selection technique used purposive sampling, which is based on criteria, with 42 companies selected using secondary data. The analytical method used was multiple linear regression analysis using SPSS version 23. The results of this study indicate that institutional ownership has an effect on financial performance, independent commissioners have no effect on financial performance, company size has no effect on financial performance, and company growth has an effect on financial performance.